2020
DOI: 10.1111/jdv.16231
|View full text |Cite
|
Sign up to set email alerts
|

The risk of treated anxiety and treated depression among patients with psoriasis and psoriatic arthritis treated with apremilast compared to biologics, DMARDs and corticosteroids: a cohort study in the United States MarketScan database

Abstract: Background Anxiety and depression are common among psoriasis and psoriatic arthritis (PsA) patients, but rates may differ by treatment. Objective To quantify the risk of incident treated anxiety, depression and mixed anxiety + depression in users of apremilast compared with users of other treatments for psoriasis and PsA. Methods We conducted two separate cohort studies of psoriasis and PsA patients treated with apremilast, tumour necrosis factor inhibitor biologics, interleukin-17,-23 or-12/23 inhibitor biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…On the other hand, short-term clinical trials reported a somewhat elevated risk of depression in apremilast users, resulting in a label warning. However, long-term data and real-world evidence suggest that users of apremilast had similar rates of depression compared with users of other systemic non-corticosteroid PsA drugs [ 118 , 119 ]. Similar considerations can be made for suicide.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, short-term clinical trials reported a somewhat elevated risk of depression in apremilast users, resulting in a label warning. However, long-term data and real-world evidence suggest that users of apremilast had similar rates of depression compared with users of other systemic non-corticosteroid PsA drugs [ 118 , 119 ]. Similar considerations can be made for suicide.…”
Section: Resultsmentioning
confidence: 99%
“… 35 , 46 , 47 However, little is known about whether systemic treatment for psoriasis is associated with an increased risk of anxiety and depression, and whether these risks differ between the various treatments. 48 …”
Section: Use Of Apremilast For Plaque Psoriasis In Special Populationsmentioning
confidence: 99%
“…The results of short-term clinical trials and post-marketing cases suggested that apremilast was associated with an elevated risk of depression, anxiety, and suicidal thoughts, to a certain extent. 48 According to post-marketing data, out of 105,000 patients who received apremilast, only 65 patients reported either depression and/or suicidal thoughts or behavior, of whom 32 patients improved after discontinuation of therapy. 49 Based on these reports, precaution is recommended when prescribing apremilast in patients with a history of depression and/or suicidal thoughts or behavior, as per prescribing information.…”
Section: Use Of Apremilast For Plaque Psoriasis In Special Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been also a growing interest in drugs used by psoriasis patients and their effects on the psychiatric disorders that accompany psoriasis Molecules 2022, 27, 1412 2 of 19 patients. While systemic corticosteroids have been associated with a high risk of depression and anxiety in psoriasis patients, biologics have been demonstrated to have the potential to reduce the risk of depression than conventional treatments such as methotrexate, cyclosporine, and systemic corticosteroids [15][16][17][18][19]. This increased the need to develop alternative medicines for psoriasis treatments to ameliorate the inflammatory skin symptoms and psychological comorbidities in the patients.…”
Section: Introductionmentioning
confidence: 99%